Great circle sailing chart of the North Atlantic Ocean. - United States. Hydrographic Office (United States. Hydrographic Office, 1926)
Annotated by Charles A. Lindbergh to show his great circle route for his New York to Paris flight in 1927. In lower right margin: No. 1280. "Small corrections . X'26." "Used in laying out Great Circle course for New York to Paris flight. San Diego, Calif. 1927. C.A.L." -- handwritten in lower right corner. Indexed in: Manuscript and annotated maps in the American Geographical Society Library: a cartobibliography. Charles Lindbergh (1902–74) was the American aviator who made the first nonstop solo flight across the Atlantic Ocean on May 21–22, 1927. This is the chart with the gnomonic projection that he referred to as the “nugget of gold” that he found in a shop in San Pedro, California, while preparing for his transatlantic flight. It was this chart that enabled Lindbergh to determine quickly and accurately the great circle latitudes and longitudes as he plotted his course. The annotation on the map reads, “Used in laying out Great Circle Course for New York to Paris flight. San Diego, Calif. 1927. C.A.L.” In his 1953 book, The Spirit of St. Louis, Lindbergh described his use of this map: “My navigating problems have begun to clarify. I found, printed on the charts I bought, ample instructions for laying out my great-circle route. With the instruments Hall loaned me, I drew a straight line between New York and Paris on the gnomonic projection. Then I transferred points from that line, at hundred-mile intervals, to the Mercator’s projection, and connected these points with straight lines. At each point, I mark down the distance from New York and the magnetic course to the next change in angle.” WDL Color